2019
DOI: 10.3390/ijms20235939
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C1: Its Pleiotropic Effects in Lipid Metabolism and Beyond

Abstract: Apolipoprotein C1 (apoC1), the smallest of all apolipoproteins, participates in lipid transport and metabolism. In humans, APOC1 gene is in linkage disequilibrium with APOE gene on chromosome 19, a proximity that spurred its investigation. Apolipoprotein C1 associates with triglyceride-rich lipoproteins and HDL and exchanges between lipoprotein classes. These interactions occur via amphipathic helix motifs, as demonstrated by biophysical studies on the wild-type polypeptide and representative mutants. Apolipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 208 publications
(221 reference statements)
4
101
0
2
Order By: Relevance
“…Apolipoprotein C1 Part of multiple apolipoprotein complexes, has links to immune response and inflammation (Fuior and Gafencu, 2019) .…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Apolipoprotein C1 Part of multiple apolipoprotein complexes, has links to immune response and inflammation (Fuior and Gafencu, 2019) .…”
Section: Supplementary Informationmentioning
confidence: 99%
“…APOC1 is a member of the apolipoprotein family that ACTS not only to transport lipids and stabilize the lipoprotein structure but also to regulate pathological processes including diabetes, Alzheimer's and inflammation. [11][12][13][14] In recent years, some studies have found that ApoA1, 15,16 ApoB, [17][18][19] ApoE 20,21 and other apolipoproteins 22 are abnormally expressed in tumors and are related to the prognosis of patients. Therefore, the role of apolipoprotein family in the occurrence and development of tumors has attracted more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Also, we detected the expression of lipid metabolism-related proteins, including Acat2 24 and LCAT. 25 Interestingly, miR-542-5p decreased the expression of Acat2 and elevated the expression of LCAT in primary hepatocytes and HepG2 cells, while anti-miR-542-5p exerted the opposite effects on the expression of Acat2 and LCAT ( Supplementary Fig. 1C , only online).…”
Section: Resultsmentioning
confidence: 93%